Development of Portrait of Uzbekistan During the Early 20thCentury - Kultashev, Bakhrom; Sadikova, Sevara; Kultasheva, Nigorakhon (The journal of contemporary issues in business and government, 2021)
The given article examines one of the insufficiently explored problems of art history of Uzbekistan – The formation of a genre system in local painting at the beginning of the 20th century through the example of portrait. Authors investigate such aspects as formation, specificity of themes and traditions, the historical and cultural situation, nature of artistic processes, its main tendencies as well as the role and influence of cultural traditions.